Hypoxia-inducible factor is expressed in giant cell tumour of bone and mediates paracrine effects of hypoxia on monocyte-osteoclast differentiation via induction of VEGF - Knowles, H; Athanasou, N (John Wiley & Sons, Ltd., 2008)
Hypoxia is an important regulator of bone biology and stimulates osteoclast differentiation from monocytic precursors. Hypoxia-inducible factor (HIF) is a key pro-tumourigenic transcription factor mediating pathways of hypoxia-inducible gene expression. We have described expression of HIF-1α and HIF-2α in the multi-nucleated, osteoclast-like giant cells and the mononuclear stromal component of giant cell tumour of bone (GCTB), a locally osteolytic primary bone tumour. HIF induction was observed in culture in the osteoblastic MG-63 cell line, primary GCTB stromal cells, and monocyte-derived osteoclasts following stimulation with hypoxia (0.1% O2) or the osteoclastogenic cytokines hepatocyte growth factor (HGF) and macrophage colony-stimulating factor (M-CSF). This was accompanied by increased expression of the downstream target genes Bcl-2/adenovirus E1B 19 kD-interacting protein 3 (BNIP3), Glut-1, and vascular endothelial growth factor (VEGF). As VEGF can substitute for M-CSF to support osteoclastogenesis in the presence of receptor activator for nuclear factor κB ligand (RANKL), we assessed the effect of MG-63 hypoxic conditioned media on osteoclast differentiation. In the presence of RANKL, hypoxic conditioned media induced the formation of active osteoclasts, as assessed from the numbers of TRAP-positive multi-nucleated cells and the area of lacunar bone resorption, which was inhibited by co-incubation with a neutralizing anti-VEGF antibody. Targeted siRNA ablated HIF-1α and/or HIF-2α expression in MG-63 cells and reduced hypoxic secretion of VEGF. Hypoxic conditioned media from cells treated with siRNA for (HIF-1α + HIF-2α) produced a significant decrease in osteoclast number (p < 0.005) and activity (p < 0.05) in comparison with the scrambled siRNA control. These results suggest that local hypoxia could indirectly influence osteoclastogenesis via autocrine and paracrine secretion of VEGF under the control of HIF. This is potentially an important mechanism of pathogenesis for GCTB and other osteolytic lesions.